Comparação do tempo de processamento entre heurísticas simuladas selecionadas em problemas de flow shop nas linguagens de programação Pascal e C - Cezario, Nathana Caroline Donini (2022)
The objective of this work is the comparative study of processing times through the simulation of the Shortest Processing Time (SPT), Longest Processing Time (LPT) and NEH heuristics adapted to solve problems for classic production systems, no idle and no wait, to find a minimization of makespan and flowtime, in a flow shop task sequencing environment. The sequencing problems of n tasks in m machines, have as objective to minimize the total time of the tasks in the machines, in order to obtain a greater efficiency in the productive process of companies, in addition to this optimization of the total time in the instances, it was also sought the optimization of the processing times of each implemented method and comparing them in two different programming languages, Pascal and C, using best practice techniques. After the analyzes measured by means of success and mean relative deviations, a better performance was found for the method in which the NEH was. In addition, it was analyzed using the percentage variance of the processing times of each method in the two programming languages, in which we can conclude that the code implemented in the programming language in C obtained a 46% reduction in processing times in relation to the methods, and in relation to systems, there was a decrease of 36%.